The faraway world : stories - Engel, Patricia (Avid Reader Press, 2023)
A collection of ten haunting short stories linked by themes of migration, sacrifice, and moral compromise bring to life the liminality of regret, the vibrancy of community, and the epic deeds and quiet moments of love.